2019
DOI: 10.1080/02602938.2019.1580674
|View full text |Cite
|
Sign up to set email alerts
|

Assessment policies and academic performance within a single course: the role of motivation and self-regulation

Abstract: Despite the frequently reported association of characteristics of assessment policies with academic performance, the mechanisms through which these policies affect performance are largely unknown. Therefore, the current research investigated performance, motivation and self-regulation for two groups of students following the same statistics course, but under two assessment policies: education and child studies (ECS) students studied under an assessment policy with relatively higher stakes, a higher performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
(74 reference statements)
2
16
0
1
Order By: Relevance
“…On the one hand, higher performance standards have consistently been associated with higher grades (Johnson and Beck 1988;Elikai and Schuhmann 2010;Kickert et al 2018Kickert et al , 2019, which should result in higher progress. Additionally, simulation studies have shown that more students progress in case of compensatory instead of conjunctive standards (Douglas and Mislevy 2010;Yocarini et al 2018).…”
Section: Performance Standardmentioning
confidence: 99%
“…On the one hand, higher performance standards have consistently been associated with higher grades (Johnson and Beck 1988;Elikai and Schuhmann 2010;Kickert et al 2018Kickert et al , 2019, which should result in higher progress. Additionally, simulation studies have shown that more students progress in case of compensatory instead of conjunctive standards (Douglas and Mislevy 2010;Yocarini et al 2018).…”
Section: Performance Standardmentioning
confidence: 99%
“…The scores of college students are closely correlated with self-discipline and time management. Good students generally have different behavior patterns from average students [20]. Therefore, the scores of college students can be reflected in daily life activities, such as smart card usage, Internet access, and cellphone/computer interactions.…”
Section: Problem Definitionmentioning
confidence: 99%
“…In order to graduate, students need to pass assessments. Hence, it has been observed that the lowest grade that students would be satisfied with is never below the passing grade, regardless of what that passing grade is (Kickert et al, 2019). In other words, although students differ in which grade they are satisfied with, all students are motivated to perform.…”
Section: Motivation In a Misaligned Curriculummentioning
confidence: 99%
“…Although we have explained that we believe all students are motivated to perform, we are not postulating that all students only want to pass. Many students wish to perform better than satisfactory (Kickert et al, 2019), and some students will want to put effort in unassessed learning, despite the curricular pressure to refrain from doing so. In fact, unassessed learning should be highly salient for students who are mindful of long-term benefits of learning.…”
Section: Curricular Fitmentioning
confidence: 99%
See 1 more Smart Citation